'Immanent Nation: The Rohingya quest for international recognition'. Issue 4 (21st August 2019) - Abraham, Itty; Jaehn, Miriam
Abstract: This paper lies at the intersection of scholarly literatures on forced migration, politically engaged diasporas, and the use of online platforms and digital technologies for political ends. It follows the efforts of a group of Rohingya diasporic activists using a variety of means, online and offline, to contest the claims and authority of Myanmar, an established territorial state. Their actions can be subsumed into two kinds of politics, a politics of confrontation and a politics of recognition. Taken together, these actions lead to an emergent political formation, a reterritorialised, dispersed, and virtual national community that seeks to mimic some state functions without explicitly calling for self‐determination or an independent nation‐state. This paper follows four activist projects: YouTube‐based Rohingya TV, the effort to join the ConIFA alternative World Football Cup tournament, the campaign to have the Rohingya script recognized by the Unicode Consortium, and the effort to build a database for undocumented Rohingyas using blockchain. This complex of social, political, electronic, and virtual relations is situated against a 20th century political imaginary built around the homeland–people–language trinity, dialectically producing an immanent contradiction.